2020
DOI: 10.1103/physrevlett.124.163603
|View full text |Cite
|
Sign up to set email alerts
|

High Quality Entangled Photon Pair Generation in Periodically Poled Thin-Film Lithium Niobate Waveguides

Abstract: We report measurements of time-frequency entangled photon pairs and heralded single photons at telecommunications wavelengths, generated using a periodically-poled, lithium niobate on insulator (LNOI) waveguide pumped optically by a diode laser. We achieve a high Coincidences-to-Accidentals Ratio (CAR) at high pair brightness, a low value of the conditional self-correlation function [g (2) (0)], and high two-photon energy-time Franson interferometric visibility, which demonstrate the high quality of the entang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
134
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(136 citation statements)
references
References 66 publications
2
134
0
Order By: Relevance
“…By incorporating longer TF-PPLN waveguides (5-mm-long poled region), Zhao et al [115] have recently reported on CAR values >67 000 with 82 kHz generation rate, as depicted in Figure 15c. CAR values of the discussed work in this section are summarized in Table 4.…”
Section: Quantum Optics On Tflnmentioning
confidence: 93%
See 1 more Smart Citation
“…By incorporating longer TF-PPLN waveguides (5-mm-long poled region), Zhao et al [115] have recently reported on CAR values >67 000 with 82 kHz generation rate, as depicted in Figure 15c. CAR values of the discussed work in this section are summarized in Table 4.…”
Section: Quantum Optics On Tflnmentioning
confidence: 93%
“…converters, [100][101][102][103][104][105][106][107][108][109][110][111] and entangled-photon sources [112][113][114][115][116] with significantly superior performances than their conventional LN counterparts have been demonstrated. The overall efforts have rejuvenated LN for novel electro-, nonlinear-, and quantum-optic applications and the material is considered among the top candidates for heterogeneous integrated photonics, where multiple materials are monolithically integrated on a single chip, while each material is chosen for the functionalities that suits it best.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, by pumping in normal dispersion regime, far-detuned photonpairs were generated in single-mode PCF with a high coincidence rate of 4.5 kHz in a simple single-pass setup with only 3 meters of PCF (8 kHz coincidence rate for a 6-meter-long PCF), with a maximum PGR of 6.7 × 10 6 pairs/s and CAR around 5 116 . In a later work, by shifting from ns-pulse pumping to ps-pulse pumping thus mitigating influence of noises due to the SpRS, with a 2-m-long PCF, PGR was increased 33,38,[175][176][177][178][179][180][181][182][183][184][185][186][187][188][189][190] 700-1260 nm 185,186 , Oband 33,175,177,178 , S-band 182,187 , Cband 38,176,[179][180][181]183,184,188,189,191 , L-band 187,190 , Mid-IR 185 250 33 67224 190 99% 178 polarization 38,178,180,1...…”
Section: Photonic Crystal Fibersmentioning
confidence: 97%
“…Time-bin entanglement has been demonstrated with doubly-resonant Ti-infused PPLN waveguide 188 . With recent advances in the fabrication of high-quality PPLN waveguides, a high brightness of 56 MHz/mw/nm (at a CAR over 600) with a maximum CAR of 67000 has been achieved 190 .…”
Section: Channel Waveguidesmentioning
confidence: 99%
“…H 0 ð Þ less than 0.025 at sub-mW pump level [62]. The shallow etched ridge waveguide was fabricated using 300-nm thick MgO-doped x-cut LNTF, and the QPM period was 2.8 μm due to a strong dispersion.…”
Section: Other Second-order Nonlinear Processesmentioning
confidence: 99%